Review Paper: Myocardial Rupture After Acute Myocardial Infarction: A review (Tanzania Medical Journal, 2008)
Myocardial rupture complications after acute myocardial infarction are infrequent but lethal. They mainly involve rupture of the ventricular free wall, ventricular septum, papillary muscle, or combined. We compare features of different kinds of myocardial ruptures after acute myocardial infarction by reviewing the clinical insights. Tanzania Medical Journal Vol. 23 (1) 2008: pp. 30-33